Phloem-specific expression of a melon Aux/IAA in tomato plants alters auxin sensitivity and plant development - Guy eGolan; Rotem eBetzer; Shmuel eWolf (Frontiers in Plant Science, 2013)
Phloem sap contains a large repertoire of macromolecules in addition to sugars, amino acids, growth substances and ions. The transcription profile of melon phloem sap contains over 1,000 mRNA molecules, most of them associated with signal transduction, transcriptional control, and stress and defense responses. Heterografting experiments have established the long-distance trafficking of numerous mRNA molecules. Interestingly, several trafficking transcripts are involved in the auxin response, including two molecules coding for auxin/indole acetic acid (Aux/IAA). To further explore the biological role of the melon Aux/IAA transcript CmF-308 in the vascular tissue, a cassette containing the coding sequence of this gene under a phloem-specific promoter was introduced into tomato plants. The number of lateral roots was significantly higher in transgenic plants expressing CmF-308 under the AtSUC2 promoter than in controls. A similar effect on root development was obtained after transient expression of CmF-308 in source leaves of N. benthamiana plants. An auxin-response assay showed that CmF-308-transgenic roots are more sensitive to auxin than control roots. In addition to the altered root development, phloem-specific expression of CmF-308 resulted in shorter plants, a higher number of lateral shoots and delayed flowering, a phenotype resembling reduced apical dominance. In contrast to the root response, cotyledons of the transgenic plants were less sensitive to auxin than control cotyledons. The reduced auxin sensitivity in the shoot tissue was confirmed by lower relative expression of several Aux/IAA genes in leaves and an increase in the relative expression of a cytokinin-response regulator, TRR8/9b. The accumulated data suggest that expression of Aux/IAA in the phloem modifies auxin sensitivity in a tissue-specific manner, thereby altering plant development.